Molecular cloning, characterization and expression of the B-xylanase cDNA gene XYN2 of the fungus Trichoderma reesei in the yeast Saccharomyces cerevisiae - La Grange, Daniël Coenrad (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1995.